SDG4 quality education : inclusivity, equity and lifelong learning for all - Ferguson, Therese; Iliško, Dzintra; Roofe, Carmel; Hill, Susan, active 2018 (Concise guides to the United Nations sustainable development goals, 2018)
Sustainable Development Goal 4 seeks to 'Ensure inclusive and equitable quality education for all and promote lifelong learning opportunities for all.' It acknowledges that quality education is a foundational necessity for sustainable development and an enhanced quality of life.SDG4 - Quality Education: Inclusivity, Equity and Lifelong Learning For All explores the multifaceted and complex nature of the concepts of inclusivity and quality education. Drawing examples from two different country contexts (Latvia and Jamaica), the book explores how and why inclusive and quality education is critical to sustainable development. It considers the indicators of inclusive and quality education, how the concept of education for sustainable development is evolving, and the ways in which these indicators are being pursued. The book pays specific attention to the roles of teachers, teacher educators, and the curriculum in the attainment of inclusive and quality education and 21st Century skills for a sustainable society. Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.